Adaptation of an in‐person dyadic care planning intervention for virtual delivery: Challenges and opportunities. (December 2021) - Orsulic‐Jeras, Silvia; Whitlatch, Carol J.; Powers, Sara
Abstract: Background: Many psychosocial interventions targeting both persons living with dementia (PWD) and their family care partners (the care dyad) have been developed and have demonstrated significant positive effects for either, or both, care partners. One such intervention, SHARE for Dementia, is an evidence‐based, 6‐session program led by a trained SHARE Counselor typically in‐person within care dyads' homes. In an effort to reach families in need of support during the Covid‐19 pandemic when home and office visits were not possible, necessary adaptations to SHARE protocols and materials were identified and piloted as a first step toward the creation of a remotely delivered version of SHARE. Method: SHARE Counselors (n = 5) from various community‐based organizations licensed to deliver the in‐person SHARE for Dementia program participated in a series of virtual adaptation meetings under the guidance of the SHARE Research Team. Result: The following areas of need for adaptation of SHARE were identified: 1) Mode of delivery (smart phones/tablets, Zoom/Skype); 2) Dissemination of intervention materials (email, use of the SHARE app for iPad); 3) Administration of Care Values and Preferences assessments; 4) Building and maintaining rapport and trust with care dyads; and 5) Remote presentation of SHARE intervention tools. Conclusion: This presentation will highlight a series of best practices and recommendations for a full‐scale adaptation of SHARE for Dementia for remote delivery. Insights from SHARE Counselors will highlight support for the use of a remote version of SHARE in non‐pandemic times to reach underserved and rural populations in need of support or for PWDs that live alone and have a long‐distance care partner. Case examples will be used to illustrate remote delivery successes and challenges as well as highlight ways SHARE can be delivered using a hybrid model to accommodate the unique needs of families that may benefit.